Advances in plant tissue culture current developments and future trends - Kumar, Ajay; Modi, Arpan; Rai, Avinash Chandra; Singh, Major (Academic Press, 2022)
"Advances in Plant Tissue Culture: Current Developments and Future Trends provides a complete and up-to-date text on all basic and applied aspects of plant tissue cultures and their latest application implications. It will be beneficial for students and early-career researchers of plant sciences and plant/agricultural biotechnology. Plant tissue culture has emerged as a sustainable way to meet the requirements of fresh produces, horticultural crops, medicinal or ornamental plants. Nowadays, plant tissue culture is an emerging filed applied in various aspects, including sustainable agriculture, plant breeding, horticulture and forestry.This book covers the latest technology, broadly applied for crop improvement, clonal propagation, Somatic hybridization Embryo rescue, Germplasm conservation, genetic conservation, or for the preservation of endangered species. However, these technologies also play a vital role in breaking seed dormancy over conventional methods of conservation."